Salivary duct carcinoma of accessory parotid - Mohammed A Al-Hashim; Nasser A Al-Jazan (Wolters Kluwer Medknow Publications, 2017)
Accessory parotid gland (APG) is seen in around 21%-56% of individuals. Tumors of accessory parotid are uncommon with an incidence rate of 1%-8% of all parotid tumors. Ductal carcinoma of APG is rare, so no reported incidence was seen in the literature. However, salivary gland ductal carcinoma is reported to be 1% of all salivary gland neoplasms. We report here a case of salivary duct carcinoma of APG. Clinical presentation, investigation, and management are discussed. A 69-year-old female presented with a history of the left cheek progressive swelling of 6 years' duration. Computed tomography and magnetic resonance imaging showed heterogeneous lobulated ill-defined mass over the left masseter. Fine needle aspiration was inconclusive. Excision of the mass showed salivary duct carcinoma. Ductal carcinoma of APG is an aggressive tumor which needs to be managed aggressively. Standard parotidectomy incision approach seems to be a safe and efficient way of management.